The year in cardiovascular medicine 2020: digital health and innovation [Год в сердечно-сосудистой медицине, 2020 г.: цифровое здравоохранение и инновации] - Antoniades, C; Asselbergs, FW; Vardas, P (Silicea - Poligraf, LLC, 2021)
Advances in digital health and particularly in artificial intelligence (AI) have led us very close to the true implementation of personalised medicine. The year 2020 has brought an exponential increase of studies using various forms of artificial intelligence, from supervised machine learning to unsupervised deep learning, with applications across all domains of Cardiovascular Medicine. AI is now moving from research to implementation, affecting all aspects of clinical Cardiology. The studies bringing AI close to clinical practice span from fast clinical and biochemical data analysis and interpretation of results, to image analysis, ECG interpretation, arrhythmia detection, or even the use of face recognition to diagnose cardiovascular diseases. We review some of the most exciting development if the field of AI in Cardiology, published from fall of 2019 up until now. The studies highlighted in this article give only a small glimpse into this booming field, creating more anticipation for what will come to clinical practice in the coming years.